Pore‐Size Distribution and Frequency‐Dependent Attenuation in Human Cortical Tibia Bone Discriminate Fragility Fractures in Postmenopausal Women With Low Bone Mineral Density. (2nd September 2021) - Armbrecht, Gabriele; Nguyen Minh, Huong; Massmann, Jonas; Raum, Kay
ABSTRACT: Osteoporosis is a disorder of bone remodeling leading to reduced bone mass, structural deterioration, and increased bone fragility. The established diagnosis is based on the measurement of areal bone mineral density by dual‐energy X‐ray absorptiometry (DXA), which poorly captures individual bone loss and structural decay. Enlarged cortical pores in the tibia have been proposed to indicate structural deterioration and reduced bone strength in the hip. Here, we report for the first time the in vivo assessment of the cortical pore‐size distribution together with frequency‐dependent attenuation at the anteromedial tibia midshaft by means of a novel ultrasonic cortical backscatter (CortBS) technology. We hypothesized that the CortBS parameters are associated with the occurrence of fragility fractures in postmenopausal women ( n  = 55). The discrimination performance was compared with those of DXA and high‐resolution peripheral computed tomography (HR‐pQCT). The results suggest a superior discrimination performance of CortBS (area under the receiver operating characteristic curve [AUC]: 0.69 ≤ AUC ≤ 0.75) compared with DXA (0.54 ≤ AUC ≤ 0.55) and a similar performance compared with HR‐pQCT (0.66 ≤ AUC ≤ 0.73). CortBS is the first quantitative bone imaging modality that can quantify microstructural tissue deteriorations in cortical bone, which occur during normal aging and the development of osteoporosis. © 2021 The Authors. JBMR Plus published by Wiley Periodicals LLC on behalf of American Society for Bone and Mineral Research.